Beyond belief : psychotherapy and religion - Stein, Samuel M. (Karnac Books, 1999)
The burden once put upon natural scientists is here shouldered by psychotherapists. This book asks whether psychotherapy can go beyond belief and gives various answers from a wide variety of people and their differing perspectives.